2020
DOI: 10.1016/j.mehy.2020.110162
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection and impact on female genital tract: An untested hypothesis

Abstract: COVID pandemic consists one of the most challenging medical realities. Apart from affecting respiratory system, current evidence has demonstrated multiorgan manifestations that SARS-Cov-2 infection may actually have. However, one of the medical hypotheses not yet thoroughly tested is the impact on female reproductive system and more specifically cervix. No large observational studies have been performed to test presence of SARS-Cov-2 in cervical samples, while potential correlation and impact on HPV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The authors also suggested that this observation should motivate further investigations to uncover what exactly is happening in patients affected by COVID-19. 6 Our report, in contrast, supports a possible negative correlation between SARS-CoV-2 and HPV infections. We hypothesized that excessive inflammatory response toward SARS-CoV-2 infection may trigger a paradoxical immune reaction resulting in regression of viral warts.…”
supporting
confidence: 54%
“…The authors also suggested that this observation should motivate further investigations to uncover what exactly is happening in patients affected by COVID-19. 6 Our report, in contrast, supports a possible negative correlation between SARS-CoV-2 and HPV infections. We hypothesized that excessive inflammatory response toward SARS-CoV-2 infection may trigger a paradoxical immune reaction resulting in regression of viral warts.…”
supporting
confidence: 54%
“…Although it is not possible to correlate SARS-COV-2 infection and the development of CIN1, dysregulation of the immune system is considered a known factor for the occurrence of cervical pathology. Thus, it is pertinent to alert patients infected by HPV and contaminated by COVID-19, to be observed more regularly to optimize early detection of lesions [1], which may have contributed to the appearance of cervical lesions. The first report of the detection of SARS-COV-2 in a vulvar lesion was published in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) preferentially affects the respiratory system, its presence has already been identified in multiple organs [1], including heart, lung, liver and pancreas. Furthermore, there is increasing evidence that the virus can also reach the genitourinary system, involving testis, ovary, vagina, uterus and placenta [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organ-and cell-specific expression of ACE2 imply its regulatory role in cardiovasculature, kidneys, and fertility. 71,72 In relation to fertility, the expression of ACE2 in the ovaries and testes suggests that it plays a regulatory role in steroidogenesis, and thus affects germ cells and reproductive health. 73 Angiotensin-converting enzyme 2 acts as the entry point into cells for several coronaviruses.…”
Section: Sars-cov-2 and Its Human Host Receptormentioning
confidence: 99%